2014
DOI: 10.1098/rsbl.2014.0279
|View full text |Cite
|
Sign up to set email alerts
|

Control of self-motion in dynamic fluids: fish do it differently from bees

Abstract: To detect and avoid collisions, animals need to perceive and control the distance and the speed with which they are moving relative to obstacles. This is especially challenging for swimming and flying animals that must control movement in a dynamic fluid without reference from physical contact to the ground. Flying animals primarily rely on optic flow to control flight speed and distance to obstacles. Here, we investigate whether swimming animals use similar strategies for self-motion control to flying animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Hence an organism's response to flow conditions, or lack thereof, will influence its travel duration, route, total energy expenditure, and whether a destination (goal) can actually be reached [ 5 , 6 ]. Not surprisingly, animals across taxa have evolved mechanisms to gauge and react to the surrounding flow [ 2 , 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence an organism's response to flow conditions, or lack thereof, will influence its travel duration, route, total energy expenditure, and whether a destination (goal) can actually be reached [ 5 , 6 ]. Not surprisingly, animals across taxa have evolved mechanisms to gauge and react to the surrounding flow [ 2 , 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding has implications for studies across other taxa: a tendency to steer away from vertical gratings does not necessarily imply a response to nasal-to-temporal pattern velocity (e.g., refs. 4,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, optic flow, the angular velocity of image motion across the retina (Gibson, 1979), provides continuous feedback to an animal about its relative velocity and distance to objects in its environment (Srinivasan et al, 1991(Srinivasan et al, , 1996. In several behavioral studies, visually guided animals, such as honeybees (Baird et al, 2005;Srinivasan et al, 1991Srinivasan et al, , 1996, Drosophila (David, 1982) and budgerigars (Bhagavatula et al, 2011), have been shown to adapt their flight trajectory and speed in response to experimental manipulation of optic flow patterns (Baird et al, 2005(Baird et al, , 2010Bhagavatula et al, 2011;Dyhr and Higgins, 2010;Linander et al, 2015;Scholtyssek et al, 2014;Srinivasan et al, 1991Srinivasan et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%